A military history of the Cold War, 1962-1991 - House, Jonathan M. 1950- (Campaigns and commanders, 2022)
"An integrated survey and analysis of a complex period of semi- and wholesale warfare during the Cold War, which explores the process by which politicians and military officers designed, organized, resourced, and deployed military organizations to deter or conduct conflicts within the context of the global antagonism between East and West."--